determine: a) (-4)^-2= b)(-2)^2=
Soluções para a tarefa
Respondido por
1
a)
![(-4)^-^2=(- \frac{1}{4} )^2=+ \frac{1}{16} (-4)^-^2=(- \frac{1}{4} )^2=+ \frac{1}{16}](https://tex.z-dn.net/?f=%28-4%29%5E-%5E2%3D%28-+%5Cfrac%7B1%7D%7B4%7D+%29%5E2%3D%2B+%5Cfrac%7B1%7D%7B16%7D+)
b)
![(-2)^2=+4 (-2)^2=+4](https://tex.z-dn.net/?f=%28-2%29%5E2%3D%2B4)
b)
miguel173:
kara da uma explicada na resposta da a) pq eu nao entendo muito os simbolos
Perguntas interessantes
Psicologia,
11 meses atrás
Ed. Física,
11 meses atrás
Sociologia,
1 ano atrás
Português,
1 ano atrás
Matemática,
1 ano atrás